I'm currently stuck with the following question:

Prove, that $\ln(2) = \lim\limits_{n \to \infty} \sum_{k=1}^n \frac{1}{n+k}$ by rewriting the left side as an Integral.

So my current thoughts are:

$\ln(2) = \int_1^2 \frac{1}{x} \mathrm{d}x$

$\lim\limits_{n \to \infty} \sum_{k=1}^n \frac{1}{n+k} = \lim\limits_{n \to \infty} \sum_{k=1}^n \frac{1}{n} \frac{1}{\frac{k}{n} + 1} = \lim\limits_{n \to 0} \sum_{k=1}^{\frac{2-1}{n}} n \frac{1}{nk + 1}$

Like this, the sum is rewritten as a step function with the width of each equidistant step decreasing. If the sum is the upper sum, I have to show, that $\frac{1}{nk+1}=\ln(1 + \frac{k+1}{n})$. How can I "get rid" if the $\ln$?


You're almost there, just use the approximation of the integral by a Riemann sum over the grid $1, 1+ 1/n,\ldots, 2$, then

$$\lim\limits_{n \to \infty} \sum_{k=1}^n \frac{1}{n} \frac{1}{\frac{k}{n} + 1}= \lim\limits_{n \to \infty} \sum_{k=1}^n \left[\left(1+\frac{k}{n}\right)-\left(1+\frac{k-1}{n}\right)\right] \frac{1}{1+\frac{k}{n}}=\int_1^2\frac{1}{x}dx.$$

  • $\begingroup$ So $\left[\left(1+\frac{k}{n}\right)-\left(1+\frac{k-1}{n}\right)\right]$ is the "width" of the subdivision and $\frac{1}{1+ \frac{k}{n}}$ is the "height" respectively. But where do I know from, that this infinite sum is equal to the Integral? $\endgroup$ – Tim Feb 1 at 17:43
  • $\begingroup$ That's the definition of the Riemann integral. And be careful: It's not an infinite sum, but the limit of a sequence of finite sums. $\endgroup$ – Mars Plastic Feb 1 at 17:48
  • $\begingroup$ Ok, thank you very much. We haven't defined the Riemann sum in our lecture yet, is there a way of solving the problem without this definition? $\endgroup$ – Tim Feb 1 at 18:15
  • $\begingroup$ OK, so how is the integral introduced (defined) in your lecture? $\endgroup$ – Mars Plastic Feb 2 at 1:20
  • $\begingroup$ We have introduced the integral with step functions: Let $\varphi$ be a step function, then the integral of $\varphi$ over $[a,b]$ is defined as $\int_a^b \varphi(x) dx = \sum_{i=1}^n c_i (x_i - x_{i-1})$. And we have the definition of the integral of a regulated function: If $(\varphi_n)$ is uniformly converging to $f$, then $\int_a^b f(x) dx = \lim\limits{n \to \infty}\int_a^b \varphi_n(x) dx$. $\endgroup$ – Tim Feb 2 at 6:53


Write it as


the limit will be $$\int_a^bf(x)dx$$

In your case, $a=0\; \; b=1, f(x)=\frac{1}{1+x}$ Or $a=1,\;b=2 \;$ and$ \; f(x)=\frac 1x.$

  • $\begingroup$ So it would be $\int_1^2 \frac{1}{x} dx = \frac{1}{n} \sum_{k=1}^n \frac{1}{1 + \frac{k}{n}}$ which is equal to my upper transformation. But how can I prove the equivalence you provided to me? $\endgroup$ – Tim Feb 1 at 17:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.